Cell-free protein synthesis and in situ immobilization of deGFP-MatB in polymer microgels for malonate-to-malonyl CoA conversion. Issue 66 (9th November 2020) - Köhler, Tony; Heida, Thomas; Hoefgen, Sandra; Weigel, Niclas; Valiante, Vito; Thiele, Julian
Abstract : We describe a bottom-up approach towards functional enzymes utilizing microgels as carriers for genetic information that enable cell-free protein synthesis, in situ immobilization, and utilization of functional deGFP-MatB. Abstract : In the present work, microgels were utilized as a cell-free reaction environment to produce a functional malonyl-CoA synthetase (deGFP-MatB) under geometry-controlled transcription and translation. Our approach combines the straight-forward optimization of overall protein yield of an E. coli -based cell-free protein synthesis (CFPS) system based on concentration screening of magnesium and potassium glutamate, DNA as well as polyethylene glycol (PEG), and its innovative usage in microgel-based production of a key enzyme of the polyketide synthesis pathway. After partial modification of the carboxyl groups of hyaluronic acid (HA) with 5′-methylfuran groups via 4-(4, 6-dimethoxy-1, 3, 5-triazin-2-yl)-4-methyl-morpholinium chloride (DMTMM)-activation, these were further functionalized with dibenzocyclooctyne (DBCO) and nitrilotriacetic acid (NTA) groups by bio-orthogonal [4+2] Diels–Alder cycloaddition to yield a bifunctional macromer. After coupling the DBCO groups with azide-functionalized DNA, containing the genetic information for deGFP-MatB, via strain-promoted azide–alkyne cycloaddition (SPAAC), the DNA-/NTA-functionalized HA macromer was utilized as base material together with maleimide-functionalized PEG (PEG-mal2 ) as the crosslinker to form bifunctional microgels utilizing water-in-oil (W/O) microemulsions. As-formed microgels were incubated with nickel sulfate to activate the NTA groups and provide binding sites for deGFP-MatB, which contained six histidine residues (His-tag) for that purpose. The optimized CFPS mixture was loaded into the microgels to initiate the formation of deGFP-MatB, which was detected by a clear increase in fluorescence exclusively inside the microgel volume. Functionality of both, the bound and the decoupled enzyme was proven by reaction with malonate to yield malonyl CoA, as confirmed by a colorimetric assay.